Wstęp - Mazan-Mazurkiewicz, Alicja; Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2023)
The introduction discusses the contents of the volume devoted to Polish crime literature. Individual articles have been characterized. The ways in which they were arranged in the volume according to different keys (thematic and genological) were also discussed.